Branding Rio de Janeiro: a semiotic analysis. Issue 6 (2nd September 2019) - Lima, Vitor; Baiocchi Antunes Corrêa, Alessandra; Zanini, Marco Tulio; Grubits de Paula Pessôa, Luís Alexandre; Reis Irigaray, Hélio Arthur
Abstract : Purpose: The purpose of this paper is to identify how a city as a brand discursively conceives and articulates relevant meanings in order to build its identity. Design/methodology/approach: The study follows a discursive semiotic approach using content from the Visit.Rio website and posts from its Facebook page. Findings: It was possible to organize the values and meanings that structure the Rio de Janeiro brand in the semiotic square. Narrative schemes that concretize the value proposition guided mainly by contemplation and experimentation situations were identified. The discursive construction of the Rio de Janeiro brand is primarily marked by the relation between nature and culture, where contrasting meanings are explored by the City Hall managers. Research limitations/implications: This study is limited to the analysis of the enunciator (Rio de Janeiro brand managers) in their process of creating and articulating the city's meanings. Future research could investigate the enunciate (public) perspective. Practical implications: Managers should consider the discursive approach since it provides a more holistic perspective on the brand-building process. The findings may contribute to the understanding, selection and articulation of the correct meanings that should be communicated to the public in order to make the city a relevant and desirable place to visit. Originality/value: This paper is based on the concept of a brand as a set of discourses grounded by meanings that are culturally conceived, which, thus, presents itself as a different approach from the traditional one, especially in research on place branding.